Hirschsprung Disease and Intestinal Neuronal Dysplasia Type B: Is There a Difference in the Clinical Presentation of These Two Diseases? - Goncalves, Anderson Cesar [UNESP]; Oliveira, Bruna Camargo de [UNESP]; Coelho, Mariana Patti Sanches [UNESP]; Caproni, Eloa Scalfi; Comes, Giovana Tuccille [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP] (Springer, 2023)
Background: Although the signs and symptoms that comprise the clinical presentation of Hirschsprung disease (HD) and intestinal neuronal dysplasia type B (IND-B) are well established, no studies have specifically compared the clinical characteristics presented by patients with these diseases. We compared the clinical pictures of patients with HD and IND-B at the time of histopathological diagnosis. Methods: This was a single-center, retrospective, analytical, and comparative study. We included 119 patients aged 0-15 years diagnosed with HD or IND-B. Information from the medical records of these patients was retrieved to obtain demographic and clinical information at the time of diagnosis. The data were compared statistically according to the characteristics of the variables. Results: Sixty-nine patients (58.0%) were diagnosed with HD, and 50 (42.0%) had IND-B. The HD group had significantly more individuals with symptom onset in the neonatal period (p = 0.001), delayed meconium clearance (p < 0.001), failure to thrive (p = 0.02), and acute complications, such as enterocolitis (p = 0.049) or acute abdominal obstruction (p = 0.031), more commonly requiring emergency surgery (p < 0.001). Patients with IND-B were diagnosed at a significantly older age (p = 0.002). They more commonly had chronic constipation as their main symptom (p = 0.004), with local complications, such as evacuation bleeding (p = 0.007). Conclusion: There were significant differences between the clinical pictures of patients with HD and IND-B. Knowledge of each disease's most common signs and symptoms can help direct diagnostic susception and initial management.
Keywords: enteric nervous system disorders; children; constipation; intestinal neuronal dysplasia type b; hirschsprung disease